Critical thinking in nursing education in Iran - Kobra Akhoundzadeh; Hoda Ahmari Tehran; Shayesteh Salehi; Zahra Abedini (مجله ایرانی آموزش در علوم پزشکی, 2011)
Introduction: Nurturing critical thinking is one of the nursing educational goals in Iran. Assessing the critical thinking ability of nurses’ and nursing students' and the effect of current instructional strategies to foster it can assist to determine the efficacy or probable inadequacy of the educational system. The present study reviews the published studies on critical thinking in nursing, in Iran. Methods: This paper reviewed studies concerning critical thinking in nursing, paying particular attention to the effect of academic education on nursing students' critical thinking ability in Iran. This systematic review searched internal resources such as Iranmedex, SID, Magiran and library sources from 2003 through 2009. Other sources such as Pubmed and Elsevier were used for discussion. The key words used were “critical thinking”, “nursing” and “nursing education”. Results: The literature review showed nurses’ and students' critical thinking ability in Iran is low. It also showed that academic education did not have a significant effect on critical thinking. Conclusion: Low critical thinking skills score of nurses and nursing students in literature review asserted that it is necessary to reassess current educational strategies. It is also essential to consider probable insufficiency of critical thinking instruments.